Communicating the Spinal Muscular Atrophy diagnosis to children and the principle of autonomy - Isabella Araujo Mota Fernandes; Renata Oliveira Almeida Menezes; Guilhermina Rego (BMC, 2022)
Abstract Introduction The trinomial relationship between physicians/children/guardians is essential in the process of communicating a disease and its prognosis. Objective Analyzing the exercise of autonomy by this trinomial relationship in communicating the diagnosis of spinal muscular atrophy (SMA).   Methodology Caregivers of SMA patients answered a questionnaire containing a structured interview and the Event Impact Scale - Revised. Results The sample comprised 50 volunteers, 94% of whom were female caregivers. Psychological trauma was predominantly reported when caregivers communicated the diagnosis to children. 22% have a high risk of post-traumatic stress, relating the feeling of unpreparedness in communicating this to the child. Conclusions It was identified that the failure in communication is the main factor for negative repercussions on the autonomy of children and their guardians, with self-reported psychological trauma, besides the high risk for post-traumatic stress syndrome.